The influence of knowledge management, entrepreneurial orientation, transformational leadership, and control management system on learning organization - Jauhara, Jauhara; Ramaditya, Muhammad (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2023)
This study aims to determine the strategy for forming an organizational learning culture at PT Bank Syariah Indonesia Branch Office Jakarta Bendungan Hilir. The independent variables used are knowledge management, entrepreneurial orientation, transformational leadership, and control management systems, while the dependent variable used is organizational learning. The method used in this study is the survey method, where data is obtained from the results of collection using a questionnaire. The population in this study were all employees of PT Bank Syariah Indonesia Branch Office Jakarta Bendungan Hilir. The sample in this study was 71 respondents. The analytical tool used is SPSS 25 with the coefficient of a determination analysis technique and hypothesis testing both partially and simultaneously. The results of this study indicate that knowledge management does not affect organizational learning, entrepreneurial orientation does not affect organizational learning, transformational leadership does not affect organizational learning, and control management systems do not affect organizational learning. Then the results of the study simultaneously show that knowledge management, entrepreneurial orientation, transformational leadership, and control management systems have a significant effect on the formation of an organization’s learning culture 71.9%. Note: This article serves as a restored version of the original content following a corruption incident. The Digital Object Identifier (DOI) has been successfully re-registered and reactivated to ensure continued accessibility and citation integrity.